2017
DOI: 10.4012/dmj.2016-107
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and biocompatibility of resin-free and resin-modified direct pulp capping materials: A state-of-the-art review

Abstract: Direct pulp capping is the placement of a dental material directly over exposed pulp to prevent dental pulp from dying and avoid the need for root canal treatments. Calcium hydroxide and calcium silicates/mineral trioxide aggregates (MTA) have been commonly used for direct pulp capping with great success clinically. In recent years, resin-modified calcium hydroxide and calcium silicates have been developed with the advantages of precise placement, command set, and superior physical strength. As pulp capping ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 44 publications
2
52
0
8
Order By: Relevance
“…Chen and Suh, on the other hand, suggested that light curable resin modified calcium silicates, such as Thera-Cal LC, have less cytotoxicity and better or comparable clinical outcomes during the 1 st week of DPC. 23 For the 1-month capping period, there was no significant difference in the inflammatory score results between the BD and TotalFill subgroups. This may be attributed to the material properties: as TotalFill creates hydroxyapatite-like precipitates, an alkaline pH comparable to BD is produced, and Ca 2+ is also released, which could be conducive to hard-tissue deposition.…”
Section: Discussionmentioning
confidence: 84%
“…Chen and Suh, on the other hand, suggested that light curable resin modified calcium silicates, such as Thera-Cal LC, have less cytotoxicity and better or comparable clinical outcomes during the 1 st week of DPC. 23 For the 1-month capping period, there was no significant difference in the inflammatory score results between the BD and TotalFill subgroups. This may be attributed to the material properties: as TotalFill creates hydroxyapatite-like precipitates, an alkaline pH comparable to BD is produced, and Ca 2+ is also released, which could be conducive to hard-tissue deposition.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, good clinical results were reported in many case reports . However, MTA also has clinical disadvantages such as poor handling, discoloration, higher cytotoxicity in its freshly mixed state and high pH during setting, long setting time, and it requires that sufficient moisture be supplied during hardening . In addition, MTA or MTA‐based materials contain trace amount of heavy metals such as arsenic .…”
Section: Introductionmentioning
confidence: 99%
“…Among denture processing methods, injection molding has always been interesting for researchers because of compensation of polymerization shrinkage due to the pressure exerted by injection of the acrylic resin. [678]…”
Section: Discussionmentioning
confidence: 99%